First‐in‐human, randomized, double‐blind, placebo‐controlled, dose escalation trial of the anti‐herpes simplex virus monoclonal antibody HDIT101 in healthy volunteers. Issue 10 (23rd July 2022) - Blank, Antje; Hohmann, Nicolas; Dettmer, Marlen; Manka‐Stuhlik, Anette; Mikus, Gerd; Stoll, Felicitas; Stützle‐Schnetz, Marlies; Thomas, Daniel; Exner, Evelyn; Schmitt‐Bormann, Beate; Schaller, Torsten; Laage, Rico; et al.
Abstract: HDIT101 is a first‐in‐class humanized monoclonal antibody recognizing a conserved epitope in glycoprotein B, a target present on the surface of herpes simplex virus 1 (HSV‐1) and HSV‐2 particles as well as on virus‐infected cells. This was a first‐in‐human, single‐center, double‐blind, placebo‐controlled trial in 24 healthy volunteers, randomized 3:1 (placebo:active) in each of the six dose levels with escalating doses up to 12, 150 mg HDIT101. HDIT101 was administered intravenously, to study safety, pharmacokinetics (PKs), and immunogenicity. HDIT101 was well‐tolerated in all recipients and no serious or severe adverse events, no infusion‐related reactions, and no events suggestive of dose limiting off‐target toxicity occurred. The mean serum exposure (area under the curve from zero to infinity [AUC0‐∞ ]) of HDIT101 showed a linear increase from 4340 h*μg/ml at a dose of 50 mg to 1, 122, 247 h*μg/ml at a dose of 12, 150 mg. No immunogenic effects following HDIT101 exposure were observed at any of the applied doses. HDIT101 demonstrated the expected PK properties of a monoclonal antibody was well‐tolerated, and could be safely administered even at excessively high doses that may be required for treatment of patients with septical HSV spread.